The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1116/1.581316
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reactor wall conditions on etch processes in inductively coupled fluorocarbon plasmas

Abstract: The influence of reactor wall conditions on the characteristics of high density fluorocarbon plasma etch processes has been studied. Results obtained during the etching of oxide, nitride, and silicon in an inductively coupled plasma source fed with various feedgases, such as CHF 3 , C 3 F 6 , and C 3 F 6 /H 2 , indicate that the reactor wall temperature is an important parameter in the etch process. Adequate temperature control can increase oxide etch selectivity over nitride and silicon. The loss of fluorocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…After a 20 min chamber 'seasoning' with an ICP P = 1400W, we noticed that the temperature meter, attached to the outside of the thick chamber walls can rise greater than 134°C (the chamber heater's thermo-couple set point is 130°C). It has been observed that the loss of fluorocarbon species to the chamber walls is reduced as the wall temperature is increased, resulting in more polymer deposition onto the wafer (Schaepkens et al, 1998). This makes sense with our data, as we show more fluorocarbon deposition on the wafer with hotter chamber walls.…”
Section: A Bsupporting
confidence: 84%
See 1 more Smart Citation
“…After a 20 min chamber 'seasoning' with an ICP P = 1400W, we noticed that the temperature meter, attached to the outside of the thick chamber walls can rise greater than 134°C (the chamber heater's thermo-couple set point is 130°C). It has been observed that the loss of fluorocarbon species to the chamber walls is reduced as the wall temperature is increased, resulting in more polymer deposition onto the wafer (Schaepkens et al, 1998). This makes sense with our data, as we show more fluorocarbon deposition on the wafer with hotter chamber walls.…”
Section: A Bsupporting
confidence: 84%
“…Patterns in the nickel masking film were transferred into the SiO 2 with an Advanced Oxide Etcher (Surface Technology Systems, PLC, Newport, UK). Before etching HAR structures, we cleaned the etching chamber with an O 2 plasma, and then 'seasoned' the chamber with the etching recipe on a blank Si wafer for 20 minutes [1]. See Table S …”
mentioning
confidence: 99%
“…3,[138][139][140][141] One important difference between ALD systems and ALE systems is the overall energy content of ALE systems, in particular if plasma is used continuously Figure 11. Review of literature data of physical sputter rates for SiO 2 versus the square-root of Ar ion energy up to energies of 400 eV.…”
Section: Issues and Needsmentioning
confidence: 99%
“…In a detailed surface model proposed by Gogolieds and Vauvert 14 , etching and deposition are taken into account for using a generalized concept for "polymer surface coverage" which is found to be equivalent to a normalized fluorocarbon film thickness covering the etched surface. In works done by Schweppes and Oehrlein [15][16][17][18][19] , nearly all the parameters of the ICP equipment and plasma that probably affect the etching process have been studied.…”
Section: Introductionmentioning
confidence: 99%